Diversity of Zooplankton in Lindu Lake Waters Central Sulawesi Province - Hartina, Siti; Trianto, Manap (Jurusan Pendidikan Biologi, Fakultas Ilmu Pendidikan, Universitas Timor, 2020)
Zooplankton is small animals that swim or float in water pools and significantly affect the life of lake aquatic organisms, especially as natural food in the development and cultivation of fish. The purpose of this study was to determine the diversity of Zooplankton species in the waters of Lake Lindu. This research was conducted in April - June 2019 using a purposive sampling method. The results obtained nine types of Zooplankton in the waters of Lake Lindu, Central Sulawesi Province, namely Daphnia sp, Epischura lacustris, Hyperia sp, Cyclops vicinus, Pseudophausia sp, Temora sp, Alonella dadayi, Nebela caudate, Brachionys havanaensis. The diversity of Zooplankton species found in the waters of Lake Lindu is 2.190 (moderate diversity level). The highest H value is at station III (Inlet) which is 2.175, and the lowest H 'value is at station II (settlements) of 2.149.